New Trends in the Molecular and Biological Basis for Clinical Oncology 2009
DOI: 10.1007/978-4-431-88663-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Nuclear Export of Cyclin D1 and Hic-5 Regulates Anchorage-Dependence of Cell Growth and Survival

Abstract: Anchorage dependence of cell growth and survival is a critical trait that distinguishes nontransformed cells from transformed cells. We demonstrate that anchorage dependence is determined by anchorage-dependent nuclear retention of cyclin D1, which is regulated by the focal adhesion protein, Hic-5, whose CRM1-dependent nuclear export counteracts that of cyclin D1. An adaptor protein, PINCH, interacts with cyclin D1 and Hic-5 and potentially serves as an interface for the competition between cyclin D1 and Hic-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Hydrogen peroxide‐inducible clone‐5 is a multidomain protein that comprises four Leu‐ and Asp‐rich LD and LIM domains and serves as a molecular adaptor in a range of cellular activities from integrin signaling at focal adhesions to transcriptional activities in the nucleus . Our recent work suggested that HIC‐5 is involved in the regulation of anchorage dependence in cell growth . In this study, we examined its involvement in tumor growth and/or metastasis using cells established from MDA‐MB‐231 breast cancer cells by viral transduction of shRNA for HIC‐5 (sequence #1 and #2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide‐inducible clone‐5 is a multidomain protein that comprises four Leu‐ and Asp‐rich LD and LIM domains and serves as a molecular adaptor in a range of cellular activities from integrin signaling at focal adhesions to transcriptional activities in the nucleus . Our recent work suggested that HIC‐5 is involved in the regulation of anchorage dependence in cell growth . In this study, we examined its involvement in tumor growth and/or metastasis using cells established from MDA‐MB‐231 breast cancer cells by viral transduction of shRNA for HIC‐5 (sequence #1 and #2).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide‐inducible clone‐5 is a molecular adaptor that features redox‐sensitive expression and functions. In particular, it traffics in and out of the nucleus with the redox‐sensitive nuclear export signal and modulates cellular responses to redox changes . In this study, we tested the possible association of the emerging role of HIC‐5 with redox changes in cells.…”
Section: Resultsmentioning
confidence: 99%
“…1). Ras activates the cycD1 promoter via an AP-1 like sequence 69 and achieves predominant cycD1 nuclear localization; as a consequence, the cells may acquire an ability for non-adherent growth 70 or anchorageindependent cell cycle progression. 71,72 For this reason, cycD1 is regarded as a mitogenic sensor that relays and amplifies extracellular growth signals.…”
Section: Mechanisms For Collaboration Of C-myc With Other Oncogenes I...mentioning
confidence: 99%
“…One of the necessary steps preceding tumor invasion of transformed epithelial cells is the detachment from its matrix attachment sites, which is controlled by integrin receptors linked to the focal adhesion complex. Detachment has been shown to lead to an increase of intracellular ROS production and is facilitated by epithelial–mesenchymal transition and loss of focal adhesions. Shibanuma and colleagues now propose that, under these conditions, HIC‐5 might be a key regulator for adapting cells to ROS‐mediated cellular stress.…”
mentioning
confidence: 99%